2000
DOI: 10.1046/j.1440-1622.2000.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Australasian Survey of Split Skin Graft Donor Site Dressings

Abstract: Most of the respondents were satisfied with their preferred dressing and were not interested in trying alternative dressings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…Although national surveys revealed that Kaltostat is the most commonly used dressing in the United Kingdom and Australia, 3,16 clinical data favor other dressing types in terms of wound healing, cost, patient comfort, and ease of use. 17,2830 We and others 13,30 found Aquacel and Kaltostat to be expensive and relatively difficult to use, as these dressings required frequent reinforcement, thus precluding their routine use for split-thickness skin graft donor sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although national surveys revealed that Kaltostat is the most commonly used dressing in the United Kingdom and Australia, 3,16 clinical data favor other dressing types in terms of wound healing, cost, patient comfort, and ease of use. 17,2830 We and others 13,30 found Aquacel and Kaltostat to be expensive and relatively difficult to use, as these dressings required frequent reinforcement, thus precluding their routine use for split-thickness skin graft donor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature has shown that impregnated fine-mesh gauze, calcium alginate, and polyurethane film are among the most commonly used dressings; however, newer materials such as hydrofibers, hydrocolloids, and foams are becoming more popular for use on split-thickness donor sites. 3,8,15,16 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute wound pain has been shown to impact patient stress and, subsequently, has a negative effect on quality of life and results in delayed wound healing . In recognition of this, a pain‐free dressing is a consistently desirable quality of a wound dressing in both adult and paediatric populations …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, large variation exists among health care professionals regarding their choice for wound dressing materials or topical agents to treat DSWs [8-10]. Based on national surveys, alginates appear to be the most commonly used primary dressing [8-10], probably due to their additional haemostatic properties [11,12]. They are followed by films, hydrofibers, silicone dressings and paraffin gauzes [8].…”
Section: Introductionmentioning
confidence: 99%